Analysis of changes in the skin due to the use of masks in health professionals (Research, Society and Development, 2023)
COVID-19 is a disease caused by the SARS-CoV-2 virus and has a high incidence of propagation, given that its main form of contagion is through the dissemination of small viral particles, aerosols. Therefore, as a measure to control the spread of the pandemic, several government institutions have established the use of face protection masks as mandatory, encouraging their use for long periods and with abundant frequency. Therefore, this descriptive study aims to identify integumentary changes generated by the prolonged use of masks by health professionals, as well as to reveal the main triggering factors that interfere with these conditions. From this, the research methodology will be the application of an online questionnaire, in order to obtain quantitative data for analysis of skin changes, their causes, and care that can be adopted to prevent the emergence of occupational dermatoses. It was found that the microclimate of the skin plays a key role in maintaining skin permeability and antimicrobial action. External and genetic factors, such as the environment, temperature and pH are means that influence the skin barrier. The work points out that the main risk factors associated with the appearance of skin changes due to the use of the mask are, duration of use greater than 8 hours a day, masks of the N95/PFF2 type and female gender, as well as the most common dermatoses. prevalent among the studied population were acne and contact dermatitis.